2010
DOI: 10.1039/b921111j
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant reversible luminescent mechanochromism of silver(i) complexes containing o-bis(diphenylphosphino)benzene and phosphinesulfide

Abstract: The Ag(I) complex with o-bis(diphenylphosphino)benzene shows reversible interconversion between blue-emitting (1b) and green-emitting (1g) materials on grinding and heating; comparison of the structure of 1b with another green-emitting crystals (2) having the same formula suggests the chromism results from intermolecular interactions between adjacent phenylene rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 31 publications
3
72
0
1
Order By: Relevance
“…[8][9][10] It has been suggested that mechanical stimuli-responsive color and luminescence changes are often associated with a metastable state that is maintained at ambient condition but switched to the initial state upon heat or solvent-induced recrystallization. [4,12] Several metal complexes with silver(I), [32] copper(I), [33] gold(I), [14a, 34-36] zinc(II), [37] or platinum(II) [17c, 38] ions have been reported to exhibit distinct mechanoluminescence or triboluminescence induced by mechanical grinding, crushing, rubbing, extruding, or pressing, which is always correlated with formation/disruption of an intermolecular metal-metal contact [33,34,36] [32,38] or a change in molecular conformation. [35] We are interested in stimuli-responsive color and luminescence changes in bis(s-acetylide)platinum(II) complexes with 5,5'-bis(trimethylsilylethynyl)-2,2'-bipyridine (Me 3 SiC CbpyC C-SiMe 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] It has been suggested that mechanical stimuli-responsive color and luminescence changes are often associated with a metastable state that is maintained at ambient condition but switched to the initial state upon heat or solvent-induced recrystallization. [4,12] Several metal complexes with silver(I), [32] copper(I), [33] gold(I), [14a, 34-36] zinc(II), [37] or platinum(II) [17c, 38] ions have been reported to exhibit distinct mechanoluminescence or triboluminescence induced by mechanical grinding, crushing, rubbing, extruding, or pressing, which is always correlated with formation/disruption of an intermolecular metal-metal contact [33,34,36] [32,38] or a change in molecular conformation. [35] We are interested in stimuli-responsive color and luminescence changes in bis(s-acetylide)platinum(II) complexes with 5,5'-bis(trimethylsilylethynyl)-2,2'-bipyridine (Me 3 SiC CbpyC C-SiMe 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are sensors for volatile organic compounds (VOCs) 337. Furthermore, a new concept of sensing motion and changes in mechanical force has recently been proposed, luminescence mechanochromism and tribochromism 3847. Vapo‐ and mechanoluminescent complexes in the solid state show reversible emission‐color changes in the visible or near‐infrared regions.…”
Section: Introductionmentioning
confidence: 99%
“…Vapo‐ and mechanoluminescent complexes in the solid state show reversible emission‐color changes in the visible or near‐infrared regions. These spectral shifts, as responses of VOCs or mechanical force, generally originate from molecular conformation changes in the solid state, e.g., metal–metal distance,322, 40, 41, 4345 coordination of VOCs,2326 trapped VOCs in a crystal lattice,2729 weak noncovalent interactions (π–π interaction, hydrogen bonding, CH–π interactions),8, 11, 19, 20, 26, 30–36, 40, 43, 47 isomerization involving polymer complexes and oligomers,37 and planarization of the conjugated ligand 46. Up to now, a number of linearly‐coordinated Au I systems have been reported as vapoluminescent compounds3, 6, 9 or mechanoluminescent materials 3941.…”
Section: Introductionmentioning
confidence: 99%
“…have found important applications as fluorescent materials in organic light-emitting diodes (OLEDs). 62, 63 Application of dppben in industrial processes dates back to 1966 when a number of phosphine ligands in the reaction of butadiene with ethylene were shown to afford 1,4-hexadiene. Dppben was the most efficient phosphine in the process.…”
Section: Carbon-carbon and Carbon-heteroatom Bond-forming Reactions Bmentioning
confidence: 99%